THE IMPLEMENTATION OF NEWS WRITING TECHNIQUE ON SOME NEWS LEADS ON WEBSITE OF STATE POLYTECHNIC OF MADIUN - Alief Sutantohadi; Yulius Hari Widodo; Titik Rahayu (Humaniora Scientia, 2022)
The lead plays an important role in providing good news for readers. The lead have the intention on attracting the reader to keep reading the news from the start till the end of the news. The lead must arise the interest, attention and curiosity in brief. This research is conducted to know the type of leads are provided on the news in the website and the news elements on the lead. This research used Qualitative Method. Based on the discussion, the writer can draw conclusion as follows; the most frequent lead used on the news on the website is the descriptive lead (46,7 %) and followed by the sequence lead ( 26,7 %), and the rest use the epigram, the cummulative, the punch, the quotation of (6,7 %) for each. The news on the website uses some different kinds and different number of news elements. All the 5 W + 1 H news elements are used on the lead on the news on the website. Most of the news use four news elements (8 data) and at least use one news elements (1 datum). However, the most frequent news element used on the lead is What (13 data) and Who (13 data). The result of the discussion showed that the news on the website of State Polytechnic of Madiun uses some different kinds of leads and also the news mostly consists of four news elements. Thus, this may make the news not only provide information in the lead but also make the readers eager to read the news.Key Words : Lead, News Element, Writing Technique